Systematic approach to the correct identification of Asplenium dalhousiae (Aspleniaceae) with their medicinal uses. Issue 4 (26th December 2018) - Zaman, Wajid; Shah, Syed Nasar; Ullah, Fazal; Ayaz, Asma; Ahmad, Mushtaq; Ali, Ashaq
Abstract: In present study, multiple microscope techniques were used for the systematics identification of the species Asplenium dalhousiae . The plant was collected from different phytogeographical and its natural habitat of Pakistan, where it shows higher diversity. Morphology, foliar epidermal anatomy, and spore morphological characters of the species were studied in detailed using multiple microscopic techniques through light microscopy (LM) and scanning electron microscopy (SEM). LM and SEM were used for the systematics identification of the species. Traditionally, the species is used in the ailment of many diseases, so the spore morphology, anatomical features, and morphological characters are relevant to describe the species taxonomy. The importance of multiple methods of taxonomic study (e.g., documentation and morphological characteristics) for characterizing herbs are important step in systematic certification to maintain the efficacy of herbal medicines. The aim of the present study is to examine the morphological, anatomical, and spore morphology of the species A. dalhousiae in more detailed for the correct taxonomic identification and their medicinal validation from Pakistan. Abstract : First reference taxonomic documentation of Asplenium dalhousiae from Pakistan for the authentication of their medicinal uses. Foliar epidermal anatomical, spore morphological characteristics based on light and scanning electron microscopic study of A. dalhousiae .